Preventing Crystal Agglomeration of Pharmaceutical Crystals Using Temperature Cycling and a Novel Membrane Crystallization Procedure for Seed Crystal Generation - Elena Simone; Rahimah Othman; Goran T. Vladisavljević; Zoltan K. Nagy (MDPI AG, 2018)
In this work, a novel membrane crystallization system was used to crystallize micro-sized seeds of piroxicam monohydrate by reverse antisolvent addition. Membrane crystallization seeds were compared with seeds produced by conventional antisolvent addition and polymorphic transformation of a fine powdered sample of piroxicam form I in water. The membrane crystallization process allowed for a consistent production of pure monohydrate crystals with narrow size distribution and without significant agglomeration. The seeds were grown in 350 g of 20:80 w/w acetone-water mixture. Different seeding loads were tested and temperature cycling was applied in order to avoid agglomeration of the growing crystals during the process. Focused beam reflectance measurement (FBRM); and particle vision and measurement (PVM) were used to monitor crystal growth; nucleation and agglomeration during the seeded experiments. Furthermore; Raman spectroscopy was used to monitor solute concentration and estimate the overall yield of the process. Membrane crystallization was proved to be the most convenient and consistent method to produce seeds of highly agglomerating compounds; which can be grown via cooling crystallization and temperature cycling.